LEGAL DILEMMA OF UNDOCUMENTED INDONESIAN MIGRANT WORKERS IN MALAYSIA: Compliance or Non-Compliance? - Sofiani, Trianah; Kamalludin, Iqbal; @ Safri, Norhamidah Binti Jarimal (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
This study explores the dilemmas faced by undocumented Indonesian migrant workers in deciding whether to comply with the law and examines the characteristics of their legal compliance and non-compliance through a multidisciplinary approach. Using a sociolegal method, interviews were conducted with purposively selected undocumented Indonesian migrant workers. Furthermore, a survey was conducted by administering questionnaires to 50 undocumented Indonesian migrant workers using online media channels. The findings reveal that undocumented Indonesian migrant workers who chose to disobey the law did so mainly because of their distrust in the legal system, rather than as a result of conscious or reflective reasoning. This is illustrated by the reasons for doubt, lack of funds, cost, fear of deportation, fear of punishment, fear of being blackmailed by officers, fear of being blocked, and fear of being unable to work abroad. Collaborative strategies and approaches based on the principles of justice, benefit, and trust are key to resolving the challenges facing undocumented Indonesian migrant workers. Fair implementation of laws and policies that provide tangible benefits to the community fosters trust in the legal system. This trust ultimately eliminates migrant workers' hesitation to comply with the law. These findings contribute to the efforts of policymakers, international organizations, and non-state actors to strengthen the governance of cross-border migration, particularly for migrant workers.